Effect of a dietary supplement composed of hydrolyzed milk proteins and vanillin on the reduction of infection and oxidative stress induced by chemotherapy. Issue 10 (14th August 2020) - Amouheydari, Mehdi; Ehsani, Mohammad Reza; Javadi, Iraj
Abstract: This study evaluates the antioxidant and antibacterial activity of a mixture of lactoferrin hydrolysate (LfH), whey protein hydrolysate (WPH) and vanillin in vitro and in vivo to design a chemoprotective supplement for reducing the infection and oxidative stress induced by chemotherapy. The designed supplement showed significant antibacterial activity against E. coli . The supplement with the highest concentration exhibited considerable antioxidant activity in (2, 2‐diphenyl‐1‐picrylhydrazyl) DPPH free radicals, (2, 2′‐azino‐bis (3‐ethylbenzothiazoline‐6‐sulfonic acid) ABTS, and reducing power assays. In the biochemical analysis of liver homogenate, the supplement 3 increased the level of enzymes Catalase (CAT), Glutathione peroxidase (GPx), Superoxide dismutase (SOD), and also the Ferric Reducing Ability of Plasma (FRAP) while decreased thiobarbituric acid reactive substances (TBARS) in comparison to paclitaxel group, indicative of activity against oxidative stress. Antibacterial and antioxidant activity of the designed supplement makes it a good candidate for use as a functional food to reduce the side effects of chemotherapy. Practical applications: A dietary supplement composed of lactoferrin hydrolysate (LfH), whey protein hydrolysate (WPH) and vanillin showed antibacterial activity against E. coli and S. aureus in vitro. The studied supplement also exhibited significant antioxidant properties in the model system and anti‐oxidative stress activity in mice exposed to paclitaxel. This supplement has a potential for use in the food matrix to reduce the chemotherapy side effects and to act as a chemoprotective agent. Abstract : A dietary supplement composed of lactoferrin hydrolysate (LfH), whey protein hydrolysate (WPH) and vanillin showed antibacterial activity against E.coli and S.aureus in vitro. The studied supplement also exhibited significant antioxidant properties in the model system and anti‐oxidative stress activity in mice exposed to paclitaxel. This supplement has a potential for use in the food matrix to reduce the chemotherapy side effects and to act as a chemoprotective agent.